2005
DOI: 10.1016/j.jcis.2005.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Surface and porosity of nanocrystalline boehmite xerogels

Abstract: Boehmite xerogels are prepared by hydrolysis of Al(OC4H9)3 followed by peptization with HNO3 (H+/Al = 0, 0.07, 0.2). XRD and TEM show that these gels are made of nanosized crystals (5-9 nm in width and 3 nm thick). According to the amount of acid, no significant differences are found in size and shape, but only in the spatial arrangement of the crystallites. Nitrogen adsorption-desorption isotherms of nonpeptized gels are of type IV, whereas isotherms of peptized gels are of type I. These isotherms are analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 34 publications
6
32
0
Order By: Relevance
“…The decomposition of organic groups and the elimination of adsorbed water in the membrane pores most likely occur in the 170-300°C range. The slower gradual weight loss (wt *12%) in the 300-450°C range may correspond to the boehmite phase transformation to cAl 2 O 3 by the elimination of OH -groups [43]. The weight loss beyond 600°C was negligible.…”
Section: Polymeric Solsmentioning
confidence: 95%
“…The decomposition of organic groups and the elimination of adsorbed water in the membrane pores most likely occur in the 170-300°C range. The slower gradual weight loss (wt *12%) in the 300-450°C range may correspond to the boehmite phase transformation to cAl 2 O 3 by the elimination of OH -groups [43]. The weight loss beyond 600°C was negligible.…”
Section: Polymeric Solsmentioning
confidence: 95%
“…This behavior is typical of porous solids with cavities in the range of mesopores radius, i.e., 1.0 to 7.5 nm. Alphonse and Courty [6] observed, for nonpeptized xerogels obtained by aluminum tri-sec-butoxide hydrolysis, that adsorption-desorption isotherms form an E-type hysteresis loop. The hysteresis loops of the WS xerogels (Fig.…”
Section: Rheological Measurements On Aluminum Hydroxide Dispersionsmentioning
confidence: 99%
“…Boehmite, pseudoboehmite, bayerite, and norstrandite were identified according to pH, temperature, and other process parameters [3]. More recently, it has been demonstrated that pseudo-boehmite is made up of micro-or nanosized crystallites of boehmite [6], and it has been argued that the large loss of ignition is due to water adsorption on them. Nanometric dried powders can be obtained from gel media through vaporization of the liquid phase.…”
Section: Introductionmentioning
confidence: 99%
“…• C to 350 • C. [10] Thermal stability of aluminum oxides prepared from gel describes [29] the following Eqn (6): …”
Section: Al 2 O 3 and Sio 2 Coatings On Carbonyl Iron Powdersmentioning
confidence: 99%
“…On the other hand, gelling in polymerized systems occurs as a result of the polymerization by chemical reaction. [9] Boehmite, aluminum oxyhydroxide (γ -AlOOH), is a precursor of alumina, and exists under two distinct forms, wellcrystallized boehmite and pseudoboehmite (also called gelatinous boehmite), [10,11] with significantly different morphologies, porosities and surfaces areas (nanocrystallized particles 8-9 nm). Boehmite nanoparticles are prepared from alumina sol that consists of aluminum tri-sec-butoxide Al(OC 4 H 9 ) 3 , water and nitric acid HNO 3 .…”
Section: Introductionmentioning
confidence: 99%